Transatlantic religion: Europe, America, and the making of modern Christianity - Aubert, Annette G.; Purvis, Zachary (Brill's series in church history and religious culture, 2021)
"Transatlantic Religion offers a new perspective on nineteenth-century American Christianity that takes into account the century's major transformations in politics, philosophy, education, and religious doctrine. The book includes previously unexamined material to explain the influences of European ideas on the intellectual diversity and cultural specifics of American Christianity. It gives readers access to a new analytical approach to the transatlantic development of religion in America, one that acknowledges the role of ecumenical and partisan religious journalism, academic-religious mentoring, profound changes in the field of scientific inquiry, and the aims of institution builders. Contributors are: Annette G. Aubert, Lee C. Barrett, Elizabeth A. Clark, Andrew Z. Hansen, Charlotte Hansen, George Harinck, Paul E. Kerry, Andrew Kloes, David Komline, Hartmut Lehmann, Mark A. Noll, C. Michael Shea, Timothy Verhoeven, Zachary Purvis"--